Addition of powdered shrimp in the formulation of snacks - da Costa, Janaina; Oliveira, Dalany; Marques, Diego; Monteiro, Antônio Roberto; Costa, José Maria (Revista Ciência Agronômica, 2019)
The aim of this study was to evaluate the acceptability of corn snacks containing different concentrations of powdered shrimp. Five snack formulations were prepared: the control (with no powdered shrimp), F1, F2, F3 and F4, with the addition of 2%, 4%, 8% and 16% powdered shrimp respectively. The raw materials were subjected to a process of thermoplastic extrusion in a single-screw extruder with 3 mm radial die. The snacks produced were evaluated for their centesimal composition, the mineral content was quantified and qualified, and the snacks then submitted to sensory analysis. The sensory parameters under evaluation were: flavour, aroma, colour, texture, overall acceptance, ideal shrimp taste and purchase intention, carried out by a panel of 107 untrained judges from the State University of Maringá. According to the results, the addition of powdered shrimp resulted in a greater increase in the protein and mineral value, especially the phosphorus content. From the acceptability of the snacks, it was found that for the sensory attributes under analysis, as well as purchase intention, the preparation of extrudates with added powdered shrimp to obtain products of sensory acceptance is viable. According to the results of the sensory analysis, the addition of 9.65% powdered shrimp to the formulation gives the product an ideal shrimp taste.